Coronary angiography in worsening heart failure: determinants, findings and prognostic implications. Issue 7 (10th August 2017) - Ferreira, João Pedro; Rossignol, Patrick; Demissei, Biniyam; Sharma, Abhinav; Girerd, Nicolas; Anker, Stefan D; Cleland, John G; Dickstein, Kenneth; Filippatos, Gerasimos; Hillege, Hans L; Lang, Chim C; Metra, Marco; et al.
Abstract : Objectives: Coronary angiography is regularly performed in patients with worsening signs and/or symptoms of heart failure (HF). However, little is known on the determinants, findings and associated clinical outcomes of coronary angiography performed in patients with worsening HF. Methods: The BIOSTAT-CHF (a systems BIOlogy Study to TAilored Treatment in Chronic Heart Failure) programme enrolled 2516 patients with worsening symptoms and/or signs of HF, either hospitalised or in the outpatient setting. All patients were included in the present analysis. Results: Of the 2516 patients included, 315 (12.5%) underwent coronary angiography within the 30 days after the onset of worsening symptoms and/or signs of HF. Subjects who underwent angiography were more often observed as inpatients, had more often an overt acute coronary syndrome, had higher troponin I levels, were younger and had better renal function (all p≤0.01). Patients who underwent coronary angiography had a lower risk of the primary outcome of death and/or HF hospitalisation (adjusted HR=0.71, 95% CI 0.57 to 0.89, p=0.003) and death (adjusted HR=0.59, 95% CI 0.43 to 0.80, p=0.001). Among the patients who underwent coronary angiography, those with a coronary stenosis (39%) had a worse prognosis than those without stenosis (adjusted HR for the primary outcome=1.71, 95% CI 1.10 to 2.64, p=0.016). Conclusions: Coronary angiography was performed in <13% of patients with symptoms and/or signs of worsening HF. These patients were remarkably different from those who did not undergo coronary angiography and had a lower risk of subsequent events. The presence of coronary stenosis on coronary angiography was associated with a worse prognosis.